(untitled) (LACCEI, 2024)
The objective of this research work is to determine the choice of a mathematical model to redesign a drilling and blasting mesh in the cut SE Nv. 1680, through the analysis of the rock mass, the analysis of the process and elements involved in drilling and blasting, and the study of the mesh that is being used, in order to optimize the drilling and blasting processes and thus increase productivity, taking as reference several studies in which productivity has been improved through the choice and correct use of one or more mathematical models. This pre-experimental, applied, retrospective and cross-sectional research, collecting data through documentary analysis, RMR, GSI, drilling and blasting parameters, and the field notebook. Analyzing the rock mass, the current drilling and blasting process, the current mesh, which allowed optimizing the process. Achieving the redesign of the mesh, which directly impacted in the optimization of the processes and increased productivity, generating a reduction of 18.87% per shot, which means a monthly saving of S/. 49140 nuevos soles in the SE Cut Nv. 1680 of the Tingo Mine in CMPSA, Pataz.